\[\boxed{\text{478\ (478).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ a^{3} + a^{2} + a + 1 =\]
\[= a^{2} \cdot (a + 1) + (a + 1) =\]
\[= (a + 1) \cdot \left( a^{2} + 1 \right).\]
\[2)\ x^{5} - 3x^{3} + 4x^{2} - 12 =\]
\[= x^{3} \cdot \left( x^{2} - 3 \right) + 4 \cdot \left( x^{2} - 3 \right) =\]
\[= \left( x^{2} - 3 \right) \cdot \left( x^{3} + 4 \right).\]
\[3)\ c^{6} - 10c^{4} - 5c^{2} + 50 =\]
\[= c^{4} \cdot \left( c^{2} - 10 \right) - 5 \cdot \left( c^{2} - 10 \right) =\]
\[= \left( c^{2} - 10 \right) \cdot \left( c^{4} - 5 \right).\]
\[4)\ y^{3} - 18 + 6y^{2} - 3y =\]
\[= \left( y^{3} + 6y^{2} \right) - (18 + 3y) =\]
\[= y^{2} \cdot (y + 6) - 3 \cdot (6 + y) =\]
\[= (y + 6) \cdot \left( y^{2} - 3 \right).\]
\[5)\ a^{2} - ab + ac - bc =\]
\[= a \cdot (a - b) + c \cdot (a - b) =\]
\[= (a - b) \cdot (a + c).\]
\[= (4ac + 3b) \cdot \left( 5a^{2}b - 7c \right).\]
\[7)\ x^{2}y^{2} + xy + axy + a =\]
\[= xy \cdot (xy + 1) + a \cdot (xy + 1) =\]
\[= (xy + 1) \cdot (xy + a).\]
\[= \left( 4x^{4} - 3y^{3} \right) \cdot \left( 6x^{2} - 11y \right)\text{.\ }\]
\[\boxed{\text{478.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[Пусть\ x\ см - длина\ \]
\[прямоугольника\ ,\ тогда\ \]
\[(x - 8)\ см - его\ ширина.\]
\[x(x - 8)\ см^{2} - исходная\ \]
\[площадь\ прямоугольника;\]
\[x + 6\ (см) - длина\ \]
\[прямоугольника\ после\ \]
\[увеличения;\]
\[x(x + 6)\ см^{2} - площадь\ \]
\[прямоугольника\ после\ \]
\[увеличения.\]
\[Площадь\ прямоугольника\ \]
\[увеличится\ на\ 72\ см^{2}.\]
\[Составим\ уравнение:\]
\[x \cdot (x - 8) + 72 =\]
\[= (x + 6) \cdot (x - 8)\]
\[- 6x = - 120\]
\[x = 20\ (см) - исходная\ длина\ \]
\[прямоугольника.\]
\[20 - 8 = 12\ (см) - исходная\ \]
\[ширина.\]
\[(20 + 12) \cdot 2 = 32 \cdot 2 =\]
\[= 64\ (см) - периметр\ \]
\[исходного\ прямоугольника.\]
\[Ответ:64\ см.\ \]